2013
DOI: 10.1177/1476750313507093
|View full text |Cite
|
Sign up to set email alerts
|

‘Community control’ in CBPR: Challenges experienced and questions raised from the Trans PULSE project

Abstract: Newer forms of community-based participatory research (CBPR) prioritize community control over community engagement, and articles that outline some of the challenges inherent in this approach to CBPR are imperative in terms of advancing knowledge and practice. This article outlines the community control strategy utilized by Trans PULSE, an Ontario-wide research initiative devoted to understanding the ways in which social exclusion, cisnormativity (the belief that transgender (trans) identities or bodies are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 21 publications
2
88
0
3
Order By: Relevance
“…Our use of coding pairs for the analysis and the CCT for interpreting the themes through an iterative process illuminated four key lessons that strengthened our collaborative approach to data collection and analysis:

CBPR recognizes the value and expertise that all partners contribute, 2 but it is critical to build community capacity to facilitate equitable participation in research. 8 Similar to previous studies, 6,12 we found that some community partners considered the academic partners to be the “experts” in qualitative data analysis and therefore, better suited to lead and complete this step in the research process. Given this dynamic, it was important to develop a process to enable GHDC members with diverse perspectives, training, and experiences to work in tandem on data analysis and interpretation.

…”
Section: Lessons Learnedsupporting
confidence: 84%
See 1 more Smart Citation
“…Our use of coding pairs for the analysis and the CCT for interpreting the themes through an iterative process illuminated four key lessons that strengthened our collaborative approach to data collection and analysis:

CBPR recognizes the value and expertise that all partners contribute, 2 but it is critical to build community capacity to facilitate equitable participation in research. 8 Similar to previous studies, 6,12 we found that some community partners considered the academic partners to be the “experts” in qualitative data analysis and therefore, better suited to lead and complete this step in the research process. Given this dynamic, it was important to develop a process to enable GHDC members with diverse perspectives, training, and experiences to work in tandem on data analysis and interpretation.

…”
Section: Lessons Learnedsupporting
confidence: 84%
“…8 Similar to previous studies, 6,12 we found that some community partners considered the academic partners to be the “experts” in qualitative data analysis and therefore, better suited to lead and complete this step in the research process. Given this dynamic, it was important to develop a process to enable GHDC members with diverse perspectives, training, and experiences to work in tandem on data analysis and interpretation.…”
Section: Lessons Learnedsupporting
confidence: 84%
“…Using a participatory analysis approach enriched and contextualized the research findings, provided an opportunity to engage with research participants in the co-construction of knowledge, 27 and is guided by current guidelines on ethical research with trans people. 28 Two participants were excluded from the analysis because they reported never accessing women-specific housing (e.g., shelters) or health services (e.g., detoxification, drop-in centers). All 32 participants had been assigned male sex at birth; however, not all identified as women and many used more than one category to describe their gender.…”
Section: Methodsmentioning
confidence: 99%
“…She ultimately finds both exclusionary and hopeful practices there. The TransPULSE network, committed to ‘building our communities through research’ is a community‐based research project that seeks to identify and respond to issues faced by trans communities particularly in terms of access to health and social services (TransPULSE, ; see also Travers et al ., ). The project has been led and implemented by Trans community members with allies.…”
mentioning
confidence: 97%